New Trends of Teaching Methodology in Embroidery Classes to Children with Intellectual Disability - Assem, Abizhanova; Berikzhan, Almukhambetov; Raushan, Kanapyanova; Ainur, Mukhanova; Kamila, Zhapalova; Taniya, Kapessova (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
One of the priority tasks of school education is the formation of personality and its basic culture, including aesthetic one. However, the influence of art on the education of a person depends to a certain extent on his aesthetic development. It brings pleasure and enjoyment only to a person who has the appropriate training and is sufficiently aesthetically educated. The task of the correctional school is to provide students with the necessary aesthetic training, to introduce them into the big world of art, to make it an effective means of learning about the surrounding reality, development of thinking and moral perfection. All of the above determines the relevance of the problem of aesthetic education of children with mental retardation in circle embroidery. Purpose of the study is theoretically substantiated and experimentally test the system of correctional and pedagogical work on the aesthetic education of younger school children with intellectual disabilities in circle embroidery classes.